The Theory and practice of Managing the child with developmental language impairment across Europe and beyond - Theodorou, Elena; Petinou, Kakia; Kambanaros, Maria (My University, 2019)
Although most children learn language relatively quickly, as many as 10 per cent of them are slow to start speaking and are said to have developmental language disorder (DLD). Children with DLD are managed by a variety of different professionals in different countries, are offered different services for different periods of time and are given a variety of different therapeutic treatments. To date, there has been no attempt to evaluate these different practices. Managing Children with Developmental Language Disorder: Theory and Practice Across Europe and Beyond does just this, reporting on the findings of a survey carried out as part of the work of COST Action IS1406, a European research network. Law and colleagues analyse the results of a pan-European survey, looking at how different services are delivered in different counties, at the cultural factors underpinning such services and the theoretical frameworks used to inform practice in different countries. The book also provides a snapshot of international practices in a set of 35 country-specific "vignettes", providing a benchmark for future developments but also calling attention to the work of key practitioners and thinkers in each of the countries investigated. This book will be essential reading for practitioners working with children with language impairments, those commissioning services and policy in the field and students of speech and language therapy.
Keywords: Behavioral Sciences; Education; Health and Social Care; Language & Literature